2012
DOI: 10.1016/j.snb.2012.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Immunosensing with artificial antibodies in organic solvents or complex matrices

Abstract: a b s t r a c tThe detection of analytes in complex matrices without labour intensive sample preparation is an important goal in analytical chemistry. In this article we would like to address this issue by transferring the selectivity of natural antibody in a cheap, robust and reusable polymer, employing a double imprinting protocol. Antibodies with the desired selectivity were used as template to generate imprinted polymer particles. These antibodies were added to a prepolymer and particles were precipitated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…They compared the binding efficiencies of template molecules with not only closely related compounds, but also some substructures in order to assess the most probable binding site in the template and MIPs (Kotova et al, 2013). Schirhagl et al (2012) developed a sensitive MIP coating on QCM microfluidic chip by transferring antigenic determinants of antibody into polymeric structures through a two-step (also called double-imprinting) molecular imprinting approach. They created MIPs for the desired antigen after synthesising sacrificial antibody imprinted polymers.…”
Section: Mips As Quenchers In Sersmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared the binding efficiencies of template molecules with not only closely related compounds, but also some substructures in order to assess the most probable binding site in the template and MIPs (Kotova et al, 2013). Schirhagl et al (2012) developed a sensitive MIP coating on QCM microfluidic chip by transferring antigenic determinants of antibody into polymeric structures through a two-step (also called double-imprinting) molecular imprinting approach. They created MIPs for the desired antigen after synthesising sacrificial antibody imprinted polymers.…”
Section: Mips As Quenchers In Sersmentioning
confidence: 99%
“…They created MIPs for the desired antigen after synthesising sacrificial antibody imprinted polymers. They also showed that it is possible to detect antigen molecules extracted into organic solvent with improved detection limits as well as in complex matrices, such as plasma or bread extract (Schirhagl et al, 2012). Suriyanarayanan et al (2013) compared the efficiency of biotinyl moiety-selective polymer films created by applying an interesting strategy using imprinting with two size regimes, the template (1 nm) and sacrificial polystyrene beads (100-800 nm), to tune the porosity of MIP film and accessibility of the template to selective binding sites.…”
Section: Mips As Quenchers In Sersmentioning
confidence: 99%
“…In 1970, Cesar Milstein and Georges K€ ohler found the method of producing the antibodies of a certain type, that is of monoclonal antibodies. Nowadays a focus of much medical research is into the production of antibodies by other means (Schirhagl et al 2012) and also the creation of chemoreceptors (Dickert et al 2001). Antibodies have already become widely used in pregnancy tests, in the diagnostics of many diseases, in laboratory experiments.…”
Section: Artificial Antibodies and Growing Opportunities To Use The Imentioning
confidence: 99%
“…Schirhagl et al [9] tried to transfer the selectivity of natural antibodies in a cheap, robust, and reusable polymer via a double-imprinting protocol. First, they used antibodies with the desired selectivity as the template to generate imprinted polymer particles.…”
Section: Mip-based Quartz Crystal Microbalance Bioassaysmentioning
confidence: 99%
“…Luminescent optical assays transform the analyte-receptor binding events into measurable light signals, such as light absorption, fluorescence/phosphorescence, bio/chemiluminescence, reflectance, Raman scattering, or refractive index. The advantages of luminescent optical assays include high sensitivity, flexibility, environmental stability, ease of miniaturization, inexpensiveness, and nondestructive analyte analysis [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%